2022
DOI: 10.1128/mbio.03084-21
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Antibiotic Adjuvant Activity

Abstract: One strategy to confront the antibiotic resistance crisis is through the development of adjuvant compounds that increase the efficacy of established drugs. A key step in the development of a natural product adjuvant as a drug is identifying the resistance process it undermines to enhance antibiotic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The choice of antibiotic exposure conditions has important implications for the sensitivity of high-throughput experiments. Thus, to enable detection of specific mechanism-related interactions, antibiotic doses were selected to inhibit 20 – 30% of growth relative to growth without antibiotics (Hogan et al 2018; Geisinger et al 2020; Bailey et al 2022), as measured by OD 600 (Figure S4 and Table 1). As controls for the synergistic combination of ceftazidime/avibactam (AVI/CAZ), each component was also used at the lower concentration present in the combination as well as higher concentrations that individually inhibited 20 – 30% of growth.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The choice of antibiotic exposure conditions has important implications for the sensitivity of high-throughput experiments. Thus, to enable detection of specific mechanism-related interactions, antibiotic doses were selected to inhibit 20 – 30% of growth relative to growth without antibiotics (Hogan et al 2018; Geisinger et al 2020; Bailey et al 2022), as measured by OD 600 (Figure S4 and Table 1). As controls for the synergistic combination of ceftazidime/avibactam (AVI/CAZ), each component was also used at the lower concentration present in the combination as well as higher concentrations that individually inhibited 20 – 30% of growth.…”
Section: Resultsmentioning
confidence: 99%
“…We found that disruption of the DsbAB, but not the DsbCD, pathway substantially increased susceptibility to many antibiotics, including β-lactams and large-scaffold antibiotics (Figure 4D). Another transposon screen by the Manoil group also found that DsbA and DsbB were important for resistance to meropenem in A. baumannii (Bailey et al 2022). Recently in E. coli , the disulfide bonds introduced by the DsbAB pathway were found to be important for stability of periplasmic proteins such as β-lactamases and MCR enzymes (mobile colistin resistance) (Furniss et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations